Looking through the eyes of Job: A transpersonal–psychological perspective - Zwan, Pieter van der (HTS teologiese studies, 2019)
The current context of a turn to the visual and the transpersonal–psychological potential of the book of Job forms the background of this study, which aimed at focusing a psychological lens on the topic of eyes in the book of Job. This approach has the potential of seeing beyond both the literal and the figurative sense of eyes in the book of Job, gaining a vision of a transcendental reality, either in or after this life. In this way, the bodily suffering experienced by the protagonist could be illuminated as a model for every recipient. By relating the eye to other body parts mentioned in the book, a texture of meanings has been woven with a complicated and intriguing subtext for the narrative of the eye in the life of Job. This wealth of value attached to the eye in the book subverts the traditionally negative attitude to the visual in monotheistic religions and resuscitates the eye to the status of even a transcendental level.